Hubungan Pengetahuan Ibu Tentang Gizi Balita Dengan Kejadian Stunting Anak Umur 36-59 Bulan Di Desa Singakerta Kabupaten Gianyar - Luh Masrini Murti; Ni Nyoman Budiani; Made Widhi Gunapria Darmapatni (Poltekkes Kemenkes Denpasar, 2020)
ABSTRACTStunting is a chronic malnutrition problem caused by insufficient nutrient intake for a long time. Stunting is caused by multi-dimensional factors one of which is influenced by mother's knowledge about nutrition of toddlers. The general objective of this research is to know the correlation between mother knowledge about toddler nutrition with stunting incidence of children aged 36-59 months in Singakerta Village of Gianyar district. This type of research is correlational analytic with case control study design. This research conducted in Singakerta Village, Ubud, Gianyar District. The sample size of this study classified into 2 groups: 40 under-five stunting case group and 40 under-five children not stunting control group. Sampling technique used non probability technique with purposive sampling method. Respondent data obtained in the form of questionnaire and height observation by age. Data analysis using chi-square test. The result of this research showed mother's knowledge about nutrition of toddler (OR = 4,846; CI = 1,882-12,482) with p-value equal to 0,001 less than 0,05 (0,001 0,05). There is a significant correlation between mother's knowledge about toddler nutrition with stunting incidence of children aged 36-59 months.Keyword : knowledge of toddler nutrition, stunting, children